(untitled) - Shiroyama, Saburo (Tokyo, 1977)
On December 23, 1948, seven men climbed the thirteen steps to the gallows. Six of them were members of the defeated Japanese military. The seventh was a civilian- Hirota Koki- a stonemason's son who had risen to become both foreign minister and prime minister. His life was that of an honest man caught up in the cogs of face; his trial was a demonstration, in Justice William O. Douglas's words, not of justice, but of political power, and he died in silence.
Keywords: Statesmen; Biography; Japan